1998
DOI: 10.1590/s0100-69911998000400004
|View full text |Cite
|
Sign up to set email alerts
|

Simpatectomia cervicotoracica por videotoracoscopia: experiência inicial

Abstract: O objetivo do presente trabalho é avaliar os resultados iniciais obtidos com a simpatectomia cervicotorácica videotoracoscópica. De outubro de 1995 a outubro de 1997 foram realizados 24 procedimentos em 14 pacientes: dez homens e quatro mulheres, com idades que variaram de 16 a 56 anos, média de 30 anos. Indicações para a operação foram: hiperidrose palmar em dez pacientes, isquemia de mão em três e causalgia em um. Nos casos de hiperidrose, a ressecção da cadeia simpática incluiu T2 e T3. Nos portadores de is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
2
6
0
4
Order By: Relevance
“…Good results using thoracoscopic sympathectomy have been presented by our group, 3 as well as in other Brazilian reports, 4 although hyperhidrosis represented a small proportion of the cases. Upon reviewing the literature, the extremely small number of hyperhidrosis cases undergoing operation in Brazil becomes evident, in comparison with other countries.…”
Section: Introductionsupporting
confidence: 76%
“…Good results using thoracoscopic sympathectomy have been presented by our group, 3 as well as in other Brazilian reports, 4 although hyperhidrosis represented a small proportion of the cases. Upon reviewing the literature, the extremely small number of hyperhidrosis cases undergoing operation in Brazil becomes evident, in comparison with other countries.…”
Section: Introductionsupporting
confidence: 76%
“…We developed this approach on the basis of the study conducted at the HC-FMUSP Hyperhidrosis Outpatient Clinic, (5) in which it was demonstrated that overweight patients had more severe compensatory hyperhidrosis in the postoperative period, a finding that was also reported in the study by Boscardim et al (4) At the HC-FMUSP Hyperhidrosis Outpatient Clinic, we initially treated axillary hyperhidrosis by resection from the second to the fourth ganglia of the thoracic sympathetic chain. (6) Subsequently, on the basis of observations made at our outpatient clinic, (7) we began to spare the second ganglion and to perform thermal Axillary hyperhidrosis is a clinical condition that causes embarrassment to patients, limiting their activities of daily living, as well as interfering with their work, leisure activities, and social activities. There is a consensus that such excessive sweating deeply affects the quality of life of the affected patients, being considered a condition capable of incapacitating them not only socially and professionally but also psychologically.…”
mentioning
confidence: 99%
“…As a consequence, in the 1990s, various studies, most conducted in Europe and Asia but and some conducted in North America, called attention to this technique. (2,3) Primary hyperhidrosis is currently the principal indication for video-assisted thoracic sympathectomy. It occurs predominantly on the hands (palmar form), in the armpits (axillary form), and on the feet (plantar form) but can also manifest in the craniofacial segment.…”
mentioning
confidence: 99%
“…(6) Initially, in our routine procedures involving this ganglion, we found that 64% of the patients presented compensatory hyperhidrosis (moderate or intense sweating) in other areas of the body, and that 4% regretted having undergone the surgical procedure. (3) The description of the method employed in the study conducted by Montessi et al is highly summarized, and there is no reference to the type of anesthesia used.…”
mentioning
confidence: 99%
See 1 more Smart Citation